(untitled) (International Journal of Food and Nutritional Sciences, 2022)
To promote agricultural productivity, the government of India has striving since independence and the green revolution encourages the use of high productivity seeds, the expansion of irrigation facilities is ensuring the availability of fertilizers, pesticides, and in this sequence, the central Government has made a provision of 9000 crore For the “Pradhan Mantri Fasal Bima Yojana”. In the 2017-18 general Budgets to promote agricultural productivity, this will increase the scope of crop protection of the farmers, which will directly benefit the farmers. Agriculture sector is the basic pillar of the Indian economy. Based on the economic survey 2017-18 data. Agriculture contributes around 17.4% to India’s GDP; along with this it also provides employments to 58% of the population of India.